Penguatan Motivasi Belajar Siswa melalui Kegiatan Lokakarya Treasure Hunt And Know Your Environtment di Desa Malangsari Kecamatan Bulu Temanggung - Robingun Suyud El Syam; Sacha Mahardika; Nanda Cahyo Saputra; Dewi Saniatun; Dede Fadli Mubarok; Susan Asasiyah; Fina Qurrotul Aini (Lembaga Pengembangan Kinerja Dosen, 2025)
This article is to capture the mentoring of the Treasure Hunt and Know Your Environment Workshop Activities in Malangsari Village, Bulu Temanggung District. The mentoring strategy goes through three stages, namely preparation, implementation and evaluation. The results of the mentoring show a positive influence on strengthening the motivation to learn for students because it makes the mind clear so that the orientation of life becomes clearer. Workshops often include challenging activities for students to think outside the box and find creative solutions to a problem. This training activity can stimulate students' analytical and critical thinking skills, so that they feel more prepared to face life's challenges. Research provides future direction for more specific themes and broader areas.